Transition to coarse-grained order in coupled logistic maps: Effect of delay and asymmetry. (October 2020) - Rajvaidya, Bhakti Parag; Deshmukh, Ankosh D.; Gade, Prashant M.; Sahasrabudhe, Girish G.
Highlights: We study transition to two band attractor state in coupled logistic maps with linear/nonlinear coupling and delay. For nonlinear coupling with even delay/ linear coupling with odd delay, we find antiferromagnetic order at critical point. For linear coupling with even delay/ nonlinear coupling with odd delay, we observe ferromagnetic order at critical point. The persistence exponent for antiferromagnetic ordering is 0.375. For ferromagnetic ordering it is 0.285. Graphical abstract: Abstract: We study one-dimensional coupled logistic maps with delayed linear or nonlinear nearest-neighbor coupling. Taking the nonzero fixed point of the map x * as reference, we coarse-grain the system by identifying values above x * with the spin-up state and values below x * with the spin-down state. We define persistent sites at time T as the sites which did not change their spin state even once for all even times till time T . A clear transition from asymptotic zero persistence to non-zero persistence is seen in the parameter space. The transition is accompanied by the emergence of antiferromagnetic, or ferromagnetic order in space. We observe antiferromagnetic order for nonlinear coupling and even delay, or linear coupling and odd delay. We observe ferromagnetic order for linear coupling and even delay, or nonlinear coupling and odd delay. For symmetric coupling, we observe a power-law decay of persistence. The persistence exponent is close to 0.375 for the transition to antiferromagnetic order and close to 0.285 for ferromagnetic order. The number of domain walls decays with an exponent close to 0.5 in all cases as expected. The persistence decays as a stretched exponential and not a power-law at the critical point, in the presence of asymmetry.